Criteria of election of postgraduate courses in graduated students of technological/humanistic/artistic professions : Subjective and contextual involvements to arrive at the conclusion of them - Kligman, Cecilia Martha (2012)
The increase in the amount of studies of postgraduate course and of its students derivatives of the demand by academic credentials in the laboral and for the personal search to specialize professionally, it is a phenomenon observed in Argentine towards the middle of years 90. To obtain the final title of these studies is a percentage far below in relation to the number of the registered people. Such reasons focused our attention to analyze so much criteria of election of postgraduate, as the subjective and contextual conditions to reach the degree. This study, of cualitative type, investigate in three Specializations, which are atended in differents nationals universities, the aspects of its organization and proposed style to study and to obtain the conclusion of studies, as the motivations of the election of the students and graduated, in three different areas: artistic, humanistic and technological. The knowledge about the logic of the organization and the particularity of the object of study of each career allows to analyze differences and similarities among them contributing some proposals to consider in formation programs; whereas the trajectories of students and graduated explain the subjective aspects that take part in the conclusion or not of the postgraduate course.